- #1

lukka

- 24

- 0

[A*,A] = (2m(h/2∏)ω)^1 [mωx - ip, mωx + ip] = (2m(h/2∏)ω)^1 {m^2ω^2 [x,x] + imω ([x,p] - [p,x]) + [p,p]}

Since we have the identity;

[x,p] = -[p,x]

can one assume that..

[x,p] - [p,x] = [x,p] - (-[x,p]) = -2[p,x]

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter lukka
- Start date

- #1

lukka

- 24

- 0

[A*,A] = (2m(h/2∏)ω)^1 [mωx - ip, mωx + ip] = (2m(h/2∏)ω)^1 {m^2ω^2 [x,x] + imω ([x,p] - [p,x]) + [p,p]}

Since we have the identity;

[x,p] = -[p,x]

can one assume that..

[x,p] - [p,x] = [x,p] - (-[x,p]) = -2[p,x]

- #2

CompuChip

Science Advisor

Homework Helper

- 4,309

- 49

That's right.

(And of course [x, x] = [p, p] = 0).

(And of course [x, x] = [p, p] = 0).

- #3

lukka

- 24

- 0

Thanks CompuChip

Share:

- Replies
- 1

- Views
- 211

- Last Post

- Replies
- 2

- Views
- 311

- Replies
- 18

- Views
- 389

- Last Post

- Replies
- 19

- Views
- 563

- Replies
- 1

- Views
- 436

- Replies
- 3

- Views
- 316

- Last Post

- Replies
- 7

- Views
- 1K

- Last Post

- Replies
- 4

- Views
- 1K

- Last Post

- Replies
- 20

- Views
- 526

- Replies
- 13

- Views
- 780